MESSA ZANDE in Style Modale Africano: Filberto Giorgetti, F.S.C. Voice partition and organ accompaniment, with chimes and trumpets ad libitum. Editrice Nigrizia, Via Meloncello, 3/3, Bologna - Basil, Brother (International Library of African Music, 1965)
pages: 85
Keywords: African Music